2016
DOI: 10.1136/jech-2016-207557
|View full text |Cite
|
Sign up to set email alerts
|

Do health checks for adults with intellectual disability reduce emergency hospital admissions? Evaluation of a natural experiment

Abstract: BackgroundAnnual health checks for adults with intellectual disability (ID) have been incentivised by National Health Service (NHS) England since 2009, but it is unclear what impact they have had on important health outcomes such as emergency hospitalisation.MethodsAn evaluation of a ‘natural experiment’, incorporating practice and individual-level designs, to assess the effectiveness of health checks for adults with ID in reducing emergency hospital admissions using a large English primary care database. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 18 publications
4
25
0
Order By: Relevance
“…26 Although only about one-half of those eligible currently receive one, 27 we have shown an association between health checks and reduced admissions for ACSCs. 28 Identifying areas where surveillance could be further improved, together with appropriate treatment reflecting their increased risk and unique health care needs, may therefore improve the overall primary care management of adults with intellectual disabilities and potentially reduce unplanned hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Although only about one-half of those eligible currently receive one, 27 we have shown an association between health checks and reduced admissions for ACSCs. 28 Identifying areas where surveillance could be further improved, together with appropriate treatment reflecting their increased risk and unique health care needs, may therefore improve the overall primary care management of adults with intellectual disabilities and potentially reduce unplanned hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
“…28 Identifying areas where surveillance could be further improved, together with appropriate treatment reflecting their increased risk and unique health care needs, may therefore improve the overall primary care management of adults with intellectual disabilities and potentially reduce unplanned hospital admissions.…”
mentioning
confidence: 99%
“…The uptake of annual health checks (AHC) remains at approximately 50%. This figure needs to be increased considering the effectiveness of AHC among people with intellectual disabilities in reducing preventable emergency admissions as shown by Carey et al () in their study looking at hospital admissions for people with an intellectual disability from across English GP practices. Authors of this review showed that emergency admissions for conditions that are potentially preventable through better clinical management (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Olsen et al (1976) found a significant difference between the treatment group (health check recipients) and the control group (non-recipients) in terms of an increase in the number of night hospitalizations for the treatment group. In a study of adults with intellectual disabilities, health check-ups reduced preventable emergency admissions (Carey et al, 2016(Carey et al, , 2017. Our empirical analyses make use of a data set that was provided by the KNHIS.…”
Section: Effects Of General Health Checks On Healthcare Utilizationmentioning
confidence: 99%